Understanding Chinese University EFL Students’ Mobile-Assisted Learning, Regional Differences and Academic Emotions - Hou, Xiaoyang; Zhang, Xiaodong (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Few studies have explored regional differences in the academic emotions of Englishas-a-Foreign-Language (EFL) students when they engage in mobile-assisted learning. To fill this gap, this qualitative study, conducted at a Chinese university, focuses on eight EFL students from different regions of China and examines their academic emotions during their 21-day learning through mobile-assisted vocabulary applications. By mainly drawing on semi-structured interviews with eight students, the qualitative study showed regional differences in academic emotions during students’ vocabulary learning through mobile applications. Students from underdeveloped cities experienced more positive emotions (such as pride, willingness, enjoyment, and admiration) than those from developed cities. Implications of the study include providing suggestions for caring for the emotional well-being of EFL students from diverse regions of China during their mobile-assisted learning.